2008
DOI: 10.1093/annonc/mdn370
|View full text |Cite
|
Sign up to set email alerts
|

Capecitabine plus oxaliplatin (XELOX) versus 5-fluorouracil/folinic acid plus oxaliplatin (FOLFOX-4) as second-line therapy in metastatic colorectal cancer: a randomized phase III noninferiority study

Abstract: XELOX is noninferior to FOLFOX-4 when administered as second-line treatment in patients with metastatic colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
109
0
9

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(135 citation statements)
references
References 18 publications
8
109
0
9
Order By: Relevance
“…Recently, more attention has been paid to combination chemotherapy of CRC with the regimen of capecitabine and oxaliplatin for safe, reliable and convenient medication. In certain randomized studies it was concluded that XELOX is non-inferior in terms of efficacy to the FOLFOX regimen in the first-line treatment of MCRC (5)(6)(7)9,11 Regarding adverse reactions during treatment, 5% of patients had Grade ≥3 hematologic toxicity, 8% of patients had Grade 3 peripheral neuropathy and 13% of patients had severe hand-foot syndrome (19). Similar results were obtained in another phase II trial that included a total of 50 patients aged ﹥70 years with MCRC, using the XELOX regimen as first-line therapy.…”
Section: Study (Year Reference) Pfs (Month) Median Os (Month) ------mentioning
confidence: 99%
“…Recently, more attention has been paid to combination chemotherapy of CRC with the regimen of capecitabine and oxaliplatin for safe, reliable and convenient medication. In certain randomized studies it was concluded that XELOX is non-inferior in terms of efficacy to the FOLFOX regimen in the first-line treatment of MCRC (5)(6)(7)9,11 Regarding adverse reactions during treatment, 5% of patients had Grade ≥3 hematologic toxicity, 8% of patients had Grade 3 peripheral neuropathy and 13% of patients had severe hand-foot syndrome (19). Similar results were obtained in another phase II trial that included a total of 50 patients aged ﹥70 years with MCRC, using the XELOX regimen as first-line therapy.…”
Section: Study (Year Reference) Pfs (Month) Median Os (Month) ------mentioning
confidence: 99%
“…Toxicity. (17) showed that xELOx was statistically as effective as FOLFOx-4 when administered as a second-line treatment in patients with metastatic colorectal cancer (median progression-free survival, 4.7 vs. 4.8 months; median overall survival, 11.9 vs. 12.5 months). In summary, the results of these Phase III studies showed that capecitabine could replace 5FU/LV infusions.…”
Section: Discussionmentioning
confidence: 99%
“…The XELOX regimen was associated with a higher frequency and severity of diarrhea, thrombocytopenia and HFS, whereas FOLFOX-4 was associated with more grade 3/4 neutropenia. However, as it was shown that the efficacies of the different treatment regimens are equivalent in metastatic gastrointestinal tumors (9)(10)(11)(12)(13)(14), the use of an oral chemotherapeutic regimen is certainly more comfortable for outpatients and thus certainly positively influences the compliance of patients.…”
Section: Discussionmentioning
confidence: 99%